HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR MATA PELAJARAN PRODUKTIF PADA SISWA KELAS XI APK DI SMK NEGERI MOJOAGUNG - RAMADHAN, IRSAD (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2014)
ABSTRACTThe use of instructional media in schools is an important factor in teaching and learning activities. These factors have a big hand in achieving the desired learning outcomes so that this research aims: (1) To determine the use of instructional media contained in SMK Mojoagung. (2) To know the results of study subjects of productive lessons in class XI APK student at SMK Mojoagung . (3) To determine the relationship the use of instructional media on the results of study subjects productive class XI APK student at SMK Mojoagung. This research includes the study of associative type. The study population which is used in this study was all students in class XI APK Mojoagung SMK that is 142 students while the number of samples used is 100 students. The data obtained in this study through interviews, documentation and questionnaires. Results of research on the Use of Learning Media can be seen the number and magnitude of 66% which means that students agree with the statement in the blank, Judging from the values of r calculated for 0.694 when compared with the value interpretation quite strong correlation (between 0.6 to 0.8). Thus it can be said that the use of Learning Media has a strong relationship with the results of the study subject productive students.Keywords: Instructional Media, Learning Outcomes